Maternal Supplementation of Clofibrate Stimulates Intestinal Fatty Acid Oxidation in Newborn Suckling Piglets. (7th June 2021) - Pike, Brandon; Hicks, Julie; Zhao, Jinan; Liu, Hsiao-Ching; Odle, Jack; Xi, Lin
Abstract: Objectives: To evaluate the effects of maternal feeding of clofibrate, a pharmaceutical PPARα agonist, on the development of intestinal fatty acid metabolism in offspring using the pig as a model. Methods: A total of 27 pregnant sows were randomly assigned into three treatment groups. Each group was fed a standard diet (3265 kcal ME/kg) supplemented with either 0, 0.25% or 0.5% clofibrate (w/w) from d 107 of gestation to d 7 of lactation. A piglet from each litter was sampled on 1, 7, 14 and 19 d of age. Fatty acid oxidation was examined in homogenates of ileum mucosa using 1 mM [1– 14 C] oleic acid as a substrate in the absence or presence of in vitro supplemented L-carnitine (1 mM), malonate (10 mM) or carnitine + malonate. Results: The metabolism of [1– 14 C] oleic acid was modified by the maternal clofibrate, and the effects varied with the dose of clofibrate and postnatal age ( p < 0.001). The 14 C accumulation in 14 CO2 increased by 2.4 fold at d7 (vs d1), but showed no difference after d7. Maternal clofibrate stimulated the 14 CO2 accumulation from d1 to d19, but the stimulation decreased with postnatal age. The 14 C accumulation in acid soluble products ( 14 C-ASP) was reduced by 8.4 fold at d7 (vs d1), and no difference was observed after d7. Maternal clofibrate increased 14 C-ASP at d1, and the effect was greater as maternal clofibrate was incremented from 0.25 to 0.5%. The 14 C accumulation in esterified products ( 14 C-ESP) was greater at d7 than d1, 14 and 19. Maternal clofibrate reduced the 14 C-ESP and, again the reduction was stronger with increasing clofibrate dose. In vitro supplementation of carnitine increased 14 CO2 by 60% and 14 C-ASP by 120%, but reduced 14 C-ESP by 39% compared to control incubations. Supplementation of malonate reduced 14 CO2 by 95% and 14 C-ESP by 44%, but no effect on 14 C-ASP was detected. Conclusions: Maternal dietary supplementation of clofibrate increases intestinal fatty acid oxidation in suckling offspring, but the increase is attenuated after one week. Inhibition of the TCA cycle reduces CO2 production without affecting ASP. The availability of carnitine could be a key element to maintain a high rate of intestinal fatty acid oxidation during the neonatal period. Funding Sources: Supported by Program of Animal Nutrition, Growth and Lactation [grant no. 2015–67015-23245/project accession no. 1005855] from the USDA NIFA.